Assessing Social Entrepreneurship in South Africa - Quacoe, Dinah; Yusheng, Kong; Quacoe, Daniel (International Journal of Economics, Business and Management Studies, 2022)
There is a growing recognition in South Africa that social enterprises can and do create the most jobs because it focuses on solving social problems and establishing economic sustainability. This article was based on a conceptual analysis aimed at assessing the development of social entrepreneurship in South Africa, as well as its prevalence and influence. We analyzed why social entrepreneurship has grown in importance and popularity in South Africa, as well as its relevance, and whether it has come to stay in South Africa. We also highlighted that the most common sources of finance for most South African social entrepreneurs are sales of goods and services, government grants, membership fees, and corporate social investment. This paper further highlighted some challenges faced by social entrepreneurs such as grant funding, which is the second major source of funding for these enterprises as well as a lack of proper buildings and equipment.